N-heterocyclic carbene-catalyzed intramolecular stetter reaction between an aldehyde and activated alkyne for easy access to chromones. - Wong, Qian Ling. (2010)
A mild and efficient method for an intramolecular carbon-carbon bond formation between sp2 carbon (aldehyde) and sp carbon (activated alkyne) has been developed using N-Heterocyclic carbene catalyst. This method allows the usage of salicylaldehyde derivatives to assemble a wide pool of chromone derivatives in a straightforward and expeditious manner. The optimized reaction conditions include the employment of a thiazolium pre-catalyst (D) in the presence of Et3N, dissolved in dry DMF solvent and stirred at room temperature for 24 hours. 17 substrates had been screened and most of them afforded promising yields of 70-85%. Furthermore, we envisage the application of this method on aliphatic systems to access more heterocycles.